A comparison of uterine natural killer cell density in the peri‐implantation period between natural cycles and hormone replacement therapy cycles. (25th June 2019) - Yang, Wen‐Jui; Chen, Xiaoyan; Zhao, Yiwei; Cheung, Wing Ching; Hsiao, Shun‐Yu; Liu, Yingyu; Law, Tracy Sze Man; Chung, Jacqueline Pui Wah; Li, Tin Chiu
Abstract: Problem: A reference range for uterine natural killer (uNK) cell density in the peri‐implantation period has recently been established in natural cycles. However, it is uncertain whether the results can be applied to hormonal replacement therapy (HRT) cycles, used increasingly in frozen‐thaw embryo replacement cycles and which is known to be capable of supporting implantation. Method of Study: A total of 183 women from two IVF centers participated in this study, including 75 women in natural cycles and 108 women in HRT cycles. All endometrial biopsies were collected precisely on the putative day of embryo implantation, namely 7 days after LH surge (LH+7) of the natural cycles or 5 days after initiation of progesterone (P+5) of the HRT cycles. Endometrial sections were immunostained for CD56 for uNK cells. Cell counting was performed by a standardized protocol, and results were expressed as percentage of positive uNK cells/total stromal cells. Results: There was no significant difference ( P > 0.05) in uNK cell density between natural cycles (median 2.28%, range 0.99%‐4.78%) and HRT cycles (median 2.55%, range 0.69%‐5.02%) in women undergoing IVF‐ET treatment on the putative day of blastocyst transfer. Using reference range from 1.2% to 4.5% for uNK cell density, there was no significant difference ( P > 0.05) in high uNK cell density proportion between natural cycles (8%, 6/75) and HRT cycles (10.2%, 11/108). Conclusion: The results indicated that the reference range for uNK cell density derived from natural cycles may apply to HRT cycles.